If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = ln(-3x) Remove parenthesis around (-3x) 2 = ln * -3x Reorder the terms for easier multiplication: 2 = -3ln * x Multiply ln * x 2 = -3lnx Solving 2 = -3lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '3lnx' to each side of the equation. 2 + 3lnx = -3lnx + 3lnx Combine like terms: -3lnx + 3lnx = 0 2 + 3lnx = 0 Add '-2' to each side of the equation. 2 + -2 + 3lnx = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3lnx = 0 + -2 3lnx = 0 + -2 Combine like terms: 0 + -2 = -2 3lnx = -2 Divide each side by '3nx'. l = -0.6666666667n-1x-1 Simplifying l = -0.6666666667n-1x-1
| -2(x-5)=-7x-25 | | 4(x-6)-27=8(x-3)-3 | | -2(x-5)=-7x+25 | | 2(x+6)=-4(x+21) | | 2xy=40 | | -2(x+5)=-7x+25 | | 2(x-4)=4(x-7) | | 35+7(x+20)=3x+47 | | 2x*4y=32 | | 3x+31=5(x+10)+25 | | ((91*0.05)+(96*0.05)+(100*0.1)+(95*0.15)+(91*0.15)+(x*0.5))=95 | | -2(x-12)=-8x-30 | | -3x+6=-6x-24 | | 2x*4y=16 | | -2(x+12)=-8x+30 | | -2x-9=-5x+24 | | 1=10-3v | | -2x+9=-5x+24 | | 6x*2=48 | | 16-2g=10 | | (x+(2+i))(x-(2-i))=0 | | 18 = h3+ 15 | | 3x+2y=y-4+5x-y | | 5x^2+y^2=1 | | 32x-12=-18 | | X+3=5+4 | | ln(3x+1)=-4 | | 27000*x-0,5=10000*x | | 14(X)+48(1-X)=47.5 | | 78(X)+47(1-X)=47.7 | | 16y-20=60-4y | | 0.4x+16.5=x-1.62 |